2009
DOI: 10.1002/j.2161-007x.2009.tb00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Religion, Ethnicity, Culture, Way of Life: Jews, Muslims, and Multicultural Counseling

Abstract: Jews and Muslims represent 2 unique cultural groups that have been relatively under-examined by multicultural counseling scholars. In this article, the authors review the recent literature on Jews and Muslims, synthesize and discuss the commonalities across these 2 groups, provide some recommendations for counseling members of these populations, and offer suggestions for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…R eligious/spiritual beliefs are an integral part of clients' worldviews (Pargament, ); when counselors match therapeutic interventions to their clients' worldviews, the therapeutic alliance is strengthened (Wampold, ). With the ever‐changing landscape of religious demographics (Pew Research Center, ) and the rise of hate crimes against religious/spiritual minority groups in the United States (Schlosser, Ali, Ackerman, & Dewey, ), counselors need to be aware of diverse religious/spiritual beliefs and practices and how these beliefs and practices may manifest in counseling (Association for Spiritual, Ethical, and Religious Values in Counseling, ; Pargament, ; Utz, ). For example, counselors, and consequently their clients, would benefit from a deeper understanding of how religious/spiritual practices, such as private prayer behaviors, are associated with mental health.…”
mentioning
confidence: 99%
“…R eligious/spiritual beliefs are an integral part of clients' worldviews (Pargament, ); when counselors match therapeutic interventions to their clients' worldviews, the therapeutic alliance is strengthened (Wampold, ). With the ever‐changing landscape of religious demographics (Pew Research Center, ) and the rise of hate crimes against religious/spiritual minority groups in the United States (Schlosser, Ali, Ackerman, & Dewey, ), counselors need to be aware of diverse religious/spiritual beliefs and practices and how these beliefs and practices may manifest in counseling (Association for Spiritual, Ethical, and Religious Values in Counseling, ; Pargament, ; Utz, ). For example, counselors, and consequently their clients, would benefit from a deeper understanding of how religious/spiritual practices, such as private prayer behaviors, are associated with mental health.…”
mentioning
confidence: 99%
“…Studies show that Jews think of themselves as both Jews and Americans (Schlosser et al, 2009), and they often feel conflicted over how to maintain their Jewish identity (Altman et al, 2010). I would speculate that most Jews do not think of themselves as being Jewish first to avoid the discussion of Whiteness, but rather often refer to themselves as Jews first because their "very existence is perennially in question" (Langman, 1995, p. 3).…”
Section: Jews As a Minority Groupmentioning
confidence: 99%
“…As I often glanced around my multicultural classrooms, I never really allowed myself to believe that I am a member of a discriminated minority group. My struggles with my Jewish identity, connections with mainstream culture, and underlying lack of acceptance (Altman et al, 2010) in an American society of Christian privilege (Schlosser, Ali, Ackerman, & Dewey, 2009) has flickered in and out of my mind throughout the duration of my studies in critical pedagogies and social justice. Because of the color of my skin, even as a Jew, I am simply seen as a White person (Langman, 1995), so how could I possibly compare myself to an African American or a Latino/Latina in today's society?…”
mentioning
confidence: 99%
“…Despite the recent overall “explosion of research on cultural and diversity issues” (Schlosser, Ali, Ackerman, & Dewey, , p. 48), however, counseling and psychotherapy scholarship has given relatively short shrift to issues of religion (Schlosser, Foley, Poltrock, & Holmwood, ). Levitt and Balkin () highlighted the fact that the multicultural movement in mental health care has emphasized secular elements of identity, such as ethnicity and nationality, to the exclusion of religious identity.…”
mentioning
confidence: 99%
“…This deficiency is especially striking considering the plethora of research indicating the crucial role of religion and spirituality in psychological well‐being (Koenig, ). Schlosser, Ali, et al () suggested that the tendency to overlook religious identity in this context is a result of Christianity's status as the majority religion in the United States and the related “Christian privilege” that permeates American culture. However, religious groups represent distinct subcultures of the greater American culture, with differing values, norms, and practices.…”
mentioning
confidence: 99%